2017
DOI: 10.1038/ncomms14233
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetically inspired asymmetric total synthesis of (+)-19-dehydroxyl arisandilactone A

Abstract: Complex natural products are a proven and rich source of disease-modulating drugs and of efficient tools for the study of chemical biology and drug discovery. The architectures of complex natural products are generally considered to represent significant barriers to efficient chemical synthesis. Here we describe a concise and efficient asymmetric synthesis of 19-dehydroxyl arisandilactone A—which belongs to a family of architecturally unique, highly oxygenated nortriterpenoids isolated from the medicinal plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…The main challenges associated with the synthesis of avenaol include the construction of a bicyclo[4.1.0]heptanone skeleton containing an all- cis -substituted cyclopropane, controlling the stereochemistry at the C8 position of the C ring, and the introduction of a C3 hydroxyl group on the A ring. The construction of bicyclo[4.1.0]heptanone skeletons has mainly been investigated in the context of constructing caged structures 26 28 . For non-caged structure, the direct synthesis of these systems has been limited to the 1,4-addition of a suitable anion of a trans -chloroallylphosphonamide 29 or Ir-catalysed or Rh-catalysed cis -selective cyclopropanation reactions 30 , 31 .…”
Section: Resultsmentioning
confidence: 99%
“…The main challenges associated with the synthesis of avenaol include the construction of a bicyclo[4.1.0]heptanone skeleton containing an all- cis -substituted cyclopropane, controlling the stereochemistry at the C8 position of the C ring, and the introduction of a C3 hydroxyl group on the A ring. The construction of bicyclo[4.1.0]heptanone skeletons has mainly been investigated in the context of constructing caged structures 26 28 . For non-caged structure, the direct synthesis of these systems has been limited to the 1,4-addition of a suitable anion of a trans -chloroallylphosphonamide 29 or Ir-catalysed or Rh-catalysed cis -selective cyclopropanation reactions 30 , 31 .…”
Section: Resultsmentioning
confidence: 99%
“…A remarkable application of a diastereoselective VMAR involving a siloxyfuran nucleophile was exploited by Han, Jiang, and co-workers in 2016 in their report on the asymmetric total synthesis of (+)-19-dehydroxyl arisandilactone A ( Scheme 143 ). 378 It was serendipitously found that the BF 3 ·Et 2 O-catalyzed VMAR between 537a and the strained polycyclic chiral aldehyde 543 afforded the arisandilactone A-precursor 544 , as a result of a one-pot tandem reaction in which a typical diastereoselective VMAR forming the Felkin intermediate 543′ was followed by an intramolecular oxa-Michael reaction that generated a new tetrahydrofuran ring by cleavage of the cyclopropane carbon–carbon bond. The newly generated stereocenters at C20, C22, and C23 within product 544 formed a syn/syn stereotriad that was later epimerized to the corresponding anti/syn platform found in the target, via a DBU-catalyzed isomerization of the butenolide moiety (not shown).…”
Section: Vinylogous Esters and Lactonesmentioning
confidence: 99%
“…Heterocyclic compounds possess fascinating complex structural architecture and are key structural motifs in an array of biologically active natural products and pharmaceutically active compounds [1], which drives the development of improved and new synthetic methodologies [2,3,4,5,6,7,8,9]. In recent years, cascade reactions [10,11,12,13,14,15,16] and bio-inspired technologies [17,18,19,20,21,22,23] have been employed to access structural complexity in compounds of biological importance.…”
Section: Introductionmentioning
confidence: 99%